2023
DOI: 10.1038/s41598-022-20381-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of anemia severity levels among children aged 6–59 months in Ethiopia: Multilevel Bayesian statistical approach

Abstract: Anemia is a widespread public health problem that affects all stages of life particularly preschool children and pregnant mothers. Anemia among children had significant impact on their growth, development, school performance and mortality. Different strategies like deworming of young children, vitamin A supplementation for children aged 6–59 months, and ferrous sulphate supplementation and provision of insecticide treated bed net for pregnant women were designed to control and prevent anemia. Also, previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Cambodia is one of the malaria-endemic areas in Southeast Asia [52]. An association between childhood anemia and inflammatory infections, which includes fever, cough, and worm infestation, has been well established [53]. The possible pathway of this association is due to iron losses during the time of infections [54].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Cambodia is one of the malaria-endemic areas in Southeast Asia [52]. An association between childhood anemia and inflammatory infections, which includes fever, cough, and worm infestation, has been well established [53]. The possible pathway of this association is due to iron losses during the time of infections [54].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Cambodia is one of the malaria-endemic areas in Southeast Asia [44]. An association between childhood anemia and inflammatory infections, which includes fever, cough, and worm infestation, has been well established [45]. The possible pathway of this association is due to iron losses during the time of infections [46].…”
Section: Resultsmentioning
confidence: 99%
“…The possible pathway of this association is due to iron losses during the time of infections [46]. One previous study reported that iron-deficiency anemia may depend on inadequate iron-rich food intake, increased iron use in the body, and iron depletion due to parasitic infection [45]. Also, previous studies have reported that malaria increases erythrocyte destruction with a simultaneous failure of the bone marrow thus jeopardizing the ability to compensate for the losses [46].…”
Section: Resultsmentioning
confidence: 99%
“…A control variable, also known as a covariate, is a variable that is included in an analysis to account for potential confounding factors or to control for their influence on the relationship between the independent and dependent variables. The control variables used in this study were generated based on literature [ 8 , 51 , 53 , 56 , 69 , 78 , 79 ] and their availability in the EDHS dataset. The sex of the child (male, female), age of the child (6–11 months, 12–23, 24–35, and 36–59 months), perceived size of the child at birth (large, average and small), received deworming medication in the last 6 month (yes, no), received iron supplementation in the last 6 months (yes, no), mother's age (< 18, 18–24, 25–34, or > = 35), mother's education (no education, primary and above), mother's current work status (yes, no), household wealth index (poor, middle, and rich), place of residence (rural, urban), and region.…”
Section: Methodsmentioning
confidence: 99%